Human cathelicidin LL‐37 and its derivative IG‐19 regulate interleukin‐32‐induced inflammation. Issue 1 (September 2014) - Choi, Ka‐Yee G.; Napper, Scott; Mookherjee, Neeloffer
Summary Human cathelicidin LL‐37 protects against infections and endotoxin‐induced inflammation. In a recent study we have shown that IG‐19, an LL‐37‐derived peptide, protects in a murine model of arthritis. Cytokine interleukin‐32 (IL‐32) is elevated and directly associated with the disease severity of inflammatory arthritis. Therefore, in this study we examined the effects of LL‐37 and IG‐19 on IL‐32‐induced responses in human peripheral blood‐derived mononuclear cells (PBMC) and macrophages. We showed that CD14+ monocytes are the primary cells that produce pro‐inflammatory tumour necrosis factor‐α (TNF‐α) following stimulation of PBMC with IL‐32. We demonstrated that LL‐37 and IG‐19 significantly suppress IL‐32‐induced production of pro‐inflammatory cytokines, e.g. TNF‐α and IL‐1β, without altering chemokine production. In contrast, LL‐37 and IG‐19 enhance the production of the anti‐inflammatory cytokine IL‐1RA. Further mechanistic studies revealed that LL‐37 and IG‐19 suppress IL‐32‐mediated phosphorylation of Fyn (Y420) Src kinase. In contrast, IL‐32‐mediated phosphorylation of AKT‐1 (T308) and MKP‐1 (S359) is not suppressed by the peptides. LL‐37 and IG‐19 alone induce the phosphorylation of MKP‐1 (S359), which is a known negative regulator of inflammation. Furthermore, the peptides induce the activity of p44/42 mitogen‐activated protein kinase, which is known to phosphorylate MKP‐1 (S359). This is the first study to demonstrate the regulation of IL‐32‐induced inflammation by LL‐37 and its derivative peptide IG‐19. The mechanistic results from this study suggest that regulation of immune‐mediated inflammation by these peptides may be controlled by the dual phosphatase MKP‐1. We speculate that LL‐37 and its derivatives may contribute to the control of immune‐mediated inflammatory diseases.